ENTREPRENEURSHIP EDUCATION AND GENERATION Z: MEDIATING EFFECTS OF EMOTIONS AND ORIENTATION ON ENTREPRENEURIAL INTENTIONS - Apriliana, Tarisya; Suwarno, Henky Lisan; Abednego, Felicia (UNIVERSITAS NEGERI SURABAYA, 2025)
In order to reach the goal of Indonesia Emas 2045, it is very important to support small and medium-sized businesses, known as MSMEs. However, looking at the unemployment rate in Indonesia, which is 7.99 million people, we see that many people still have a hard time finding jobs, even though they could start their own businesses. This research wants to look at how teaching entrepreneurship can boost the desire to become an entrepreneur, with the help of entrepreneurial mindset and positive feelings among university students. This research is a type of study that can be confirmed. The group of people studied in this research includes undergraduate students from Maranatha Christian University, and the sample includes 172 students who are currently taking or have already taken entrepreneurship classes. The way the samples were chosen was through a method called non-probability sampling with purposive sampling, and information was gathered by handing out surveys. The data collected were analyzed using the Smart PLS software. The study's findings show that education in entrepreneurship does not have a direct effect on the desire to become an entrepreneur. However, entrepreneurship education does positively affect feelings and the entrepreneurial mindset. Therefore, the study concludes that education in entrepreneurship influences the desire to become an entrepreneur, with the help of an entrepreneurial mindset and positive feelings. The results of this research highlight how important these four factors are in the world of entrepreneurship.